Analisis Preferansi Konsumen Pada Produk Gatsby Face Care PT. Mandom Indonesia tbk - Hastuti, Sri; Gunawan, Tri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
This research aims to examine and analyze the Customer Preference Analysis on Gatsby facial care products of PT Mandom Indonesia Tbk, the effect of Personal Selling on Brand Image, the effect of Price on Brand Image, the effect of Personal Selling on Customer Preference, the effect price on Customer Preference and the effect of Brand Image on the Customer Preference of Gatsby Face Care Product. The design used on this research is descriptive quantitative research with causality using 151 respondents as the sample and technique the non probability sampling. Model testing are used for data analysis using Stuctural Equation Modeling with Lisrel 9 consists of CFA (Factor Confirmatori) test by factor standard loading> 0.60 and GOF (Goodness of fit) based on existing criteria where p-value> 0.05 and RMSEA <0.08.Furthermore, to test hypothesis 1, hypothesis 2, hypothesis 3, hypothesis 4 and hypothesis 5 based on the output of the Structural Equation by considering an t table value for alfa = 0.05 is 1.96 and t table for alpha = 0.10 is 1.65. The results of processing and data analysis, found that the variable of Personal Selling effect on Brand Image of 2.64, Price has no effect on Brand Image of 1.03 and Personal Selling affect the consumer preference 3.87, Price does not have effect on consumer preferences -0.42. While the Brand Image effect on Consumer Preferences 6.17.